2021
DOI: 10.3389/fmech.2021.641995
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Under-Water Compressed Air Energy Storage (UWCAES) to Fully Power the Sicily Region (Italy) With Renewable Energy: A Case Study

Abstract: The high concentration of CO2 in the atmosphere and the increase in sea and land temperatures make the use of renewable energy sources increasingly urgent. To overcome the problem of non-programmability of renewable sources, this study analyzes an energy storage system consisting of under water compressed air energy storage (UWCAES). A case study for fully power the Sicily region (Italy) with renewable energy source (wind and photovoltaic) is presented. From the real annual capacity values of the renewable pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This was explored by Hydrostor of Canada in [108], using water bags placed on the sea floor. Using similar principle, the authors of [154] proposed underground pumped storage in which surface-reservoir-stored fluid can flow via gravity to maintain the pressure of air trapped in the shafts of disused mines. The authors of [155] used a surface reservoir as a pressure-compensating water column.…”
Section: Passive Isobaric Storagementioning
confidence: 99%
“…This was explored by Hydrostor of Canada in [108], using water bags placed on the sea floor. Using similar principle, the authors of [154] proposed underground pumped storage in which surface-reservoir-stored fluid can flow via gravity to maintain the pressure of air trapped in the shafts of disused mines. The authors of [155] used a surface reservoir as a pressure-compensating water column.…”
Section: Passive Isobaric Storagementioning
confidence: 99%
“…During peakhours the air can be released and converted back to electrical power to make sure that there is no curtailment in the renewable source. Storing fresh air in salt caverns is a proven, reliable and safe method of ensuring that excess energy is not wasted [72][73][74][75]. The authors of [76] compared CAES and battery energy storage systems based on a levelized cost of storage.…”
Section: Compressed Air Energy Storage (Caes)mentioning
confidence: 99%
“…It was found that an efficiency of 59% was achievable in terms of UWCAES subsystem [44]. Tiano and Rizzo from the University of Salerno investigated the feasibility of carbon-free renewable energy feeding in Sicily by introducing UWCAES [45]. Guandalini et al from Polytechnic University of Milan conducted a preliminary design and performance assessment of UWCAES considering the off-design properties of the overall system and realistic power input.…”
Section: Adiabatic Uwcaesmentioning
confidence: 99%